Respuesta :

Answer

f(x) = (x - 4)² - 67

Explanation

We are asked to rewrite this function using the completing the square method.

f(x) = x² - 8x - 51

The first step in completing the square is to add and subtract the square of the half of the coefficient of x to the equation.

The coefficient of x = -8

Half of the coefficient of x = (-8/2) = -4

Square of the half of the coefficient of x = (-4)² = 16

f(x) = x² - 8x + 16 - 51 - 16

f(x) = x² - 8x + 16 - 67

f(x) = (x - 4)² - 67

Hope this Helps!!!

ACCESS MORE
EDU ACCESS
Universidad de Mexico